Investigation of double-mode operation and fast fine tuning properties of a grating-coupled external cavity diode laser configuration. (January 2017) - Bayrakli, Ismail
Abstract: Double-mode operation and fast piezo fine tuning properties of a gain chip on a thermoelectric cooler in an external cavity are investigated. A widely course double-mode tuning range of 120 nm for the spectral range between 1470 and 1590 nm is achieved by rotating the diffraction gratings forming a double Littrow-type configuration. A fast piezo fine tuning range over 7 cm − 1 (1.5 nm, 210 GHz) in a single-mode operation is obtained by scanning the external cavity length with scan rates up to 0.5 kHz. Abstract : Highlights: A widely double-mode tuning range of 120 nm is achieved. A fast piezo fine tuning range over 7 cm -1 (1.5 nm, 210 GHz) is obtained. Scan rates up to 0.5 kHz are reached.